Structural, microstructural, optical and electrical properties of (Pb,Ba,Sr)TiO3 films growth on conductive LaNiO3-coated LaAO(3)(100) and Pt/Ti/SiO2/Si substrates - Pontes, D. S. L.; Capeli, R. A. [UNESP]; Garzim, M. L. [UNESP]; Pontes, F. M. [UNESP]; Chiquito, A. J.; Longo, E. [UNESP] (Elsevier B.V., 2014)
The ferroelectric and dielectric properties of lead barium strontium titanate (PBST) thin films are investigated on different bottom electrode and substrate such as Pt, LaNiO3 and Pt/Ti/SiO2/Si, LaAlO3(100), respectively. X-ray diffraction results indicate that the PBST and LaNiO3 films on LaAlO3(100) single crystal substrate are highly (100)-oriented whereas the PBST films on Pt/Ti/SiO2/Si are polycrystalline. The results indicate strong effects of bottom electrode on the dielectric permittivity and tunability of the PBST films. The dielectric permittivity and tunability for the highly (100)-oriented PBST films on LaNiO3/LaAlO3(100) structure were 1238% and 65%, respectively, at 100 kHz, while PBST films prepared on PtiTi/SiO2/Si substrate, showed a dielectric permittivity of 520 and tunability of 47%, at 100 kHz. A slight shift of the phase transition temperature to lower temperatures was observed for highly (100)-oriented films in comparison to the polycrystalline films. Electrical properties should depend strongly on orientation and bottom electrode, which is reflected in our experimental observations. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Thin films; Ferroelectric; Texture; Chemical solution deposition